2018
DOI: 10.1038/s41467-018-05497-7
|View full text |Cite
|
Sign up to set email alerts
|

Azole-induced cell wall carbohydrate patches kill Aspergillus fumigatus

Abstract: Azole antifungals inhibit the fungal ergosterol biosynthesis pathway, resulting in either growth inhibition or killing of the pathogen, depending on the species. Here we report that azoles have an initial growth-inhibitory (fungistatic) activity against the pathogen Aspergillus fumigatus that can be separated from the succeeding fungicidal effects. At a later stage, the cell wall salvage system is induced. This correlates with successive cell integrity loss and death of hyphal compartments. Time-lapse fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 34 publications
7
58
0
1
Order By: Relevance
“…The effects of olorofim (and some of caspofungin's effects) on the cell wall are in contrast to those recently observed following voriconazole treatment of A. fumigatus [31]. Geiβel et al observed the formation of carbohydrate patches containing β-1,3-glucan and chitin at specific sites in the hyphae.…”
Section: Discussionmentioning
confidence: 90%
“…The effects of olorofim (and some of caspofungin's effects) on the cell wall are in contrast to those recently observed following voriconazole treatment of A. fumigatus [31]. Geiβel et al observed the formation of carbohydrate patches containing β-1,3-glucan and chitin at specific sites in the hyphae.…”
Section: Discussionmentioning
confidence: 90%
“…The number of drugs available to treat fungal infections is limited, and those that are commonly used often suffer from being fungistatic rather than fungicidal [ 2 , 3 ]. Azoles, the first-line antifungals used in the clinic, are one of these fungistatic classes of drug [ 4 , 5 , 6 ]; they can decrease the production of ergosterol by inhibiting cytochrome P450 enzyme Erg11 and by damaging the cell membrane [ 7 , 8 , 9 ]. The fungistatic nature of the azoles coupled with their extensive use has resulted in azole resistance in populations of various pathogenic fungi [ 4 , 6 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This leads us to speculate that even relatively small increases in ergosterol content in the cell membrane may lead to large increases in azole resistance via an indirect effect on azole transporter levels. Given the pleiotropic nature of the NCT complex, we cannot exclude that further factors may be contributing to the high levels of azole resistance evident in the nctA and nctB null mutants especially in light of our evidence showing that they are hypersensitive to the cell wall acting agents, and recent data showing a link between reductions in β-1,3-glucan synthesis and the delayed fungicidal effects of voriconazole 70 . The most striking phenotypes that we have observed for the nctA and the nctB null mutants aside from the resistance to the azole class of antifungals is their resistance to the salvage therapeutic amphotericin B and terbinafine, which can be used in the management of patients with chronic or allergic disease 19 .…”
Section: Discussionmentioning
confidence: 88%